Centroid-amenities: An interactive visual analytical tool for exploring and analyzing amenities in Singapore - SIEW, Xue Qian Jazreel (Institutional Knowledge at Singapore Management University, 2018)
Planning for civic amenities in a fast-changing urban setting such as Singapore is never an easy task. And as urban planners look toward more data-driven approaches toward urban planning, so grows the demand for more flexible geospatial analytics tools to facilitate a more iterative and granular approach toward urban planning. Such specific tools however, are not always readily available as plugins for traditional desktop GIS software, as numerous customizations must be made to model specific temporal planning scenarios for quick analysis, which could prove both costly and time-consuming. Hence, to address this need, open-source tools such as R Shiny could be used to rapidly prototype and test urban planning models, in an iterative fashion. To demonstrate how this could be done, we developed a proof-of-concept that aims to provide urban planners with an open-source, interactive geospatial analytics tool to help optimize the placement of amenities and services through K-means clustering, making them as accessible as possible to the city residents they serve. The platform also allows planners to compare the accessibility of the existing amenities and services, against a suggested set of optimized amenity locations, using the Hansen Accessibility Score as a measure of accessibility. This allows planners a tangible grasp on how much of an impact and improvement a relocation of amenities could make for the residents served. This paper details our research and development efforts to design and implement an open-source web-based geospatial tool for supporting the analysis of the accessibility of amenities and services.